Kajian Imageability dan Permeability Kawasan Pecinan Kesawan di Kota Medan - Azhar Hutasuhut, Alvin; Mirsa, Rinaldi; Fidyati, Fidyati (Jurnal Etnik: Ekonomi-Teknik, 2023)
Kesawan Chinatown is an urban area in the city of Medan, specifically in the Kesawan District. This area is a Chinatown district that refers to a city area outside of China where the majority of its inhabitants are of Chinese ethnicity. The area offers opportunities for tourists and local residents to learn more about colonial-era buildings. It is also an office, culinary, and other building areas. Some famous locations in this area include Tjong A Fie, the Post Office, the London Sumatra Building, and many other well-known buildings. This research aims to assess the imageability and permeability in Kesawan Chinatown. Imageability is the physical quality of a city that can create a strong image in the minds of observers. Permeability, on the other hand, refers to one's ability to access a specific location in a relatively close and easy manner in terms of time and distance. This research uses a descriptive research method with a qualitative research design (qualitative description) and mental mapping based on the city image theory used, along with sampling techniques using snowball sampling. The results of the research indicate that Kesawan Chinatown has a city image with good visual quality in terms of paths, nodes, edges, districts, and landmarks, and the permeability regarding block accessibility, path width, and path connections is excellent, making Kesawan Chinatown an easily legible area.